Insights into active travel levels at two universities. A comparative study in Ireland and Romania - Constantin Ion Alexandru; Mullan Elaine; Luca Oana; McGregor Alisha; Abdulal Nadia; Rotaru George (E3S Web of Conferences)
Levels of active travel (walking and cycling) to Southeast Technological University (SETU) and Technical University of Civil Engineering Bucharest (UTCB) are very low. A significant transition from car dependent travel to active modes of transportation for work, school and college is essential in order to meet climate action carbon reduction targets and to increase physical activity levels. Currently, the majority of students traveling to SETU and UTCB rely on private cars, which is environmentally unsustainable. First, students were surveyed about their mode of travel to university and the key barriers and enablers of walking and cycling, then, students discussed these issues in focus groups. Next, there was engagement between the students in the two universities about these results. Finally, there was discussion between students and the local authority engineers and planners in their respective cities to discuss this and plan appropriate actions. The majority of students at both universities reported that they primarily used private cars to travel to campus, citing convenience, lack of safe cycling infrastructure, and the distance from their homes as key barriers to active travel. However, many students expressed a willingness to walk or cycle if improvements were made to infrastructure, such as dedicated cycle lanes and pedestrian paths.